The Efficacy of Magic Card Games on Eaely Hijaiyah Letter Childhood Recognition - Ramadani, Wulan; Nurhayati, Nurhayati; Amrullah, Amrullah; Agusniatih, Andi (Journal of Educational Sciences, 2025)
This study discusses the problem of inadequate development in recognizing Hijaiyah letters. The purpose of this study is to find out the effectiveness of magic card games for young children in recognizing Hijaiyah letters. The research method used is quantitative, in particular, experimental studies. The subjects consisted of 13 children, 7 boys and 6 gils, from Group B1 of the Samporoa Pembina State Kindergarten. Data collection techniques include observation, documentation, and interviews. Based on the recapitulation of the initial and final observations regarding the ability to recognize the last Hijaiyah before and after the intervention, the category of "Very Well Developed" (BSB), increased from 0% to 30.76%, while the category "Not Developed" (BB), decreased from 46.15% to 0%. In addition, the BSB category increased from 0% to 15.38%, and BB decreased from 53.84% to 0% in the aspect of compiling Hijaiyah letters. In the aspect of pronouncing Hijaiyah letters, the BSB category increased from 7.6% to 38.46%, while BB decreased from 23.7% to 0%. This implies the positive effect of the magic card game on the ability to recognize Hijaiyah letters among early childhood students in Group B1 of the Samporoa Pembina State Kindergarten.